An Open Source Solution for Money Bill Recognition for the Visually Impaired User using Smartphones - Lang, Lucía (2018)
According to estimates made by the World Health Organization there are approximately 285 million people with visual disabilities. In Argentina, it is estimated that there are about 6 thousand blind people per million inhabitants. These people must face daily different situations that generate physical and psychological tension conditioning their quality of life. In particular in Argentina, one of these situations is to recognize and correctly differentiate the denomination of Argentine money bills. The current system used is heavily affected by the usage of the money bills. In this paper, we present the design and development of a novel application for mobile phones that automatically recognize money bills and credit cards. The application was design with the assistance of a visually impaired user. abstract environment.